2020
DOI: 10.1002/cbic.202000444
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Substrate Scope of the Flavin‐Dependent Halogenase BrvH

Abstract: The recently described flavin-dependent halogenase BrvH is able to catalyse both the bromination and chlorination of indole, but shows significantly higher bromination activity. BrvH was annotated as a tryptophan halogenase, but does not accept tryptophan as a substrate. Its native substrate remains unknown. A predictive model with the data available for BrvH was analysed. A training set of compounds tested in vitro was docked into the active site of a complete protein model based on the X-ray structure of Brv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…In this study, we found primarily genomic patterns that determine the enzymatic activity toward tryptophan (Trp-FDH versus non-Trp-FDH) and the site of halogenation for tryptophan (5-, 6-, and 7-Cl/Br-Trp-FDH). Recent studies found that the sequences with different substrate scope were clustered based on the sequence similarity in the network analysis ( 19 ) and screened the halogenation with various substrates ( 65 ). Structure analysis of the known proteins identified the residues that bind to FAD and substrates ( 66 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found primarily genomic patterns that determine the enzymatic activity toward tryptophan (Trp-FDH versus non-Trp-FDH) and the site of halogenation for tryptophan (5-, 6-, and 7-Cl/Br-Trp-FDH). Recent studies found that the sequences with different substrate scope were clustered based on the sequence similarity in the network analysis ( 19 ) and screened the halogenation with various substrates ( 65 ). Structure analysis of the known proteins identified the residues that bind to FAD and substrates ( 66 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacophore model was adapted from a virtual screening methodology for BrvH, and revealed 19 compounds halogenated by BrvH [52]. SpH1 is highly similar to BrvH and clusters within one clade with BrvH.…”
Section: Determination Of Halogenation Activity and Substrate Scopementioning
confidence: 99%
“…The activities of PrnF and ADH were determined as published by Frese et al [3]. The halogenation activities of SpH1 and SpH2 towards different substrates were carried out for 48 h at 25 • C and 500 rpm in a total volume of 0.5 mL, containing 1.25 mg/mL enzyme, 1 mM substrate, 1 µM FAD, 100 µM NAD, 100 mM NaBr/NaCl, RR-ADH (2 U/mL) PrnF (2.5 U/mL), 5% (v/v) iso-propanol, and 100 mM Na 2 HPO 4 buffer (pH 7.4) [33,52]. Samples were quenched by adding an equal volume of methanol.…”
Section: Enzymatic Halogenation/enzyme Assay With Purified Protein On An Analytical Scalementioning
confidence: 99%
See 1 more Smart Citation
“…To improve the utility of promiscuous enzymes, studies have implemented rational enzyme engineering, directed evolution and synthetic biology to assess and improve substrate scope (Glenn et al, 2011;Payne et al, 2015;Shepherd et al, 2015;Neubauer et al, 2020), regio-specificity (Lang et al, 2011;Andorfer et al, 2016;Shepherd et al, 2016;Moritzer et al, 2019), stability (Payne et al, 2013;Poor et al, 2014;Minges et al, 2020) and activity (Andorfer et al, 2016(Andorfer et al, , 2017Kong et al, 2020) of FDH halogenases (Table 3). Of particular interest are a study deploying directed evolution to yield RebH variants targeting positions 5, 6, and 7 of tryptamine (Andorfer et al, 2016), which could help to avoid the tryptophan decarboxylase bottleneck, and a study in which the substrate specificity of RebH was evolved to target, albeit with lower activities, "latestage" MIAs such as the yohimbines (Payne et al, 2015), which may allow promiscuity requirements to be eschewed entirely.…”
Section: New-to-nature Monoterpenoid Indole Alkaloidsmentioning
confidence: 99%